Regulation of the small GTPase Rab1 function by a bacterial glucosyltransferase. Issue 1 (December 2018) - Wang, Zhen; McCloskey, Alix; Cheng, Sen; Wu, Mei; Xue, Chenyu; Yu, Zhengyou; Fu, Jiaqi; Liu, Yanhua; Luo, Zhao-Qing; Liu, Xiaoyun
Abstract Posttranslational modification of key host proteins by virulence factors is an important theme in bacterial pathogenesis. A remarkable example is the reversible modifications of the small GTPase Rab1 by multiple effectors of the bacterial pathogenLegionella pneumophila . Previous studies have shown that the effector SetA, dependent on a functional glucosyltransferase domain, interferes with host secretory pathways. However, the enzymatic substrate(s) of SetA in host cells remains unknown. Here, by using cross-linking mass spectrometry we uncovered Rab1 as the target of SetA duringL. pneumophila infection. Biochemical studies establish that SetA covalently attaches a glucose moiety to Thr75 within the switch II region of Rab1, inhibiting its intrinsic GTPase activity. Moreover, we found that SetA preferentially modifies the GDP-bound form of Rab1 over its GTP-associated state and the modification of Rab1 inhibits its interaction with the GDP dissociation inhibitor GDI1, allowing for Rab1 activation. Our results thus add an extra layer of regulation on Rab1 activity and provide a mechanistic understanding of its inhibition of the host secretory pathways as well as cellular toxicity.